Efektifitas Penggunaan Media Video Tutorial Rias Wajah terhadap Hasil Belajar Siswa Kelas Kecantikan MAN Temanggung - Vania Divayanti Nitbani; Ifa Nurhayati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Learning in beauty classes at MAN Temanggung is still dominated by lecture methods and the use of books, so that students are easily bored and lack understanding of practical materials that require visualization. To overcome these problems, this study aims to analyze the effectiveness of video tutorial media in improving students' understanding and learning outcomes on makeup materials. The research uses a qualitative method with observation, interview, and documentation techniques for beauty class students as research subjects. The results of the study show that the use of video tutorials is able to provide clearer visualization, increase learning interest, make it easier for students to follow the steps of decoration, and support various learning styles. Video media also allows students to access the material flexibly, so that the learning process becomes more optimal. The conclusion of this study is that video tutorials are an effective learning medium and should be applied in learning makeup, because they are able to improve students' understanding of concepts and practical skills.